Perancangan Sistem Pengaduan Masyarakat untuk Mempermudah Pelaporan Permasalahan Lingkungan Warga Pademangan Barat Jakarta Utara - Muhammad Kaisar Stevan Priadi; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
Environmental problems in RT 16/RW 07, West Pademangan Village, North Jakarta, often require fast and precise handling. However, an unstructured manual reporting process hampers the communication of citizen complaints to the authorities. To overcome this, this research aims to design and develop a web-based public complaint system that makes it easier to report environmental problems. This system was developed using the prototyping method, which allows iterative development based on input from users. With this approach, the system can be more easily adapted to the needs of residents and local officials. The development process includes needs analysis, user interface design, and repeated testing of system functionality to ensure effectiveness and efficiency in delivering reports. The results of this research show that a web-based complaint system is able to increase citizen participation in reporting environmental problems and speed up the follow-up process from local authorities. This system is expected to be an efficient solution and can be implemented on a wider scale.